Calculated electron impact dissociation cross sections for molecular chlorine (Cl2). (18th September 2018) - Hamilton, James R; Tennyson, Jonathan; Booth, Jean-Paul; Gans, Timo; Gibson, Andrew R
Abstract: Electron impact dissociation of Cl2 is a key process for the formation of Cl atoms in low-temperature plasmas used for industrial etching processes. Despite this, relatively little cross section data exist for this process. In this work, electron impact dissociation cross sections were calculated for Cl2 molecules using the UK molecularR -matrix code in the low electron energy range and extended to high energies using a scaling depending on the specific nature of each transition. Our results are compared with both previous calculations and with experimental measurements, and the similarities and differences are discussed. In addition, the rate coefficients for electron impact dissociation of Cl2 are calculated by integrating the cross sections derived in this (and previous) work, with electron energy distribution functions representative of those normally found in low-temperature plasmas used in industry. Depending on the shape and effective temperature of the distribution function, significant differences arise between the rate coefficients calculated from our cross sections and those calculated using previous data. Deviations between the two sets of rate coefficients are particularly pronounced at the low electron temperatures typical of electron beam and remote plasma sources of interest for atomic layer etching and deposition. These differences are principally caused by the higher energy resolution in the near-threshold region in this work, emphasising the importance of accurate, high-resolution cross sections in this energy range.